2016
DOI: 10.1016/j.actamat.2016.06.031
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alloying nickel with iron on the supersonic ballistic stage of high energy displacement cascades

Abstract: a b s t r a c tPrevious experimental and theoretical studies suggest that the production of extended defect structures by collision cascades is inhibited in equiatomic NiFe, in comparison to pure Ni. It is also known that the production of such extend defect structures results from the formation of subcascades by high-energy recoils and their subsequent interaction. A detailed analysis of the ballistics of 40 keV cascades in Ni and NiFe is performed to identify the formation of such subcascades and to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…Recent studies indicate that high chemical complexity, as present, e.g., in high entropy alloys, can significantly enhance the performance of materials under radiation [2,106,107]. Studies for point defect properties in concentrated alloys becomes then of great importance [85,107,108].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that high chemical complexity, as present, e.g., in high entropy alloys, can significantly enhance the performance of materials under radiation [2,106,107]. Studies for point defect properties in concentrated alloys becomes then of great importance [85,107,108].…”
Section: Discussionmentioning
confidence: 99%
“…To understand defect evolution and reveal the relevant mechanisms, calculations and simulations have become a common supplement to experiment. The primary damage production process is typically addressed by molecular dynamics (MD) simulations [2,3,4,5], while the recovery stage generally requires simulations going beyond the time scale accessible with MD. To go to large time scales, rate theory [6], kinetic Monte Carlo [7,8], or cluster dynamics [9] are used.…”
Section: Introductionmentioning
confidence: 99%
“…10,41 Sluggish and chemically-biased diffusion for interstitial atom migration, and positive Niinterstitial atom transport coefficients, were demonstrated by ab initio and classical MD, k-ART, and kMC modeling in the equiatomic Ni-Fe alloy. 38,39 Thus, atomic-scale modeling and theory unambiguously predict that, under irradiation, interstitial atoms drag Ni atoms along their diffusion paths, while the vacancy flux provides Fe atom transport in the opposite direction. These mechanisms lead to a segregation bias in interactions among mobile defects (vacancies, interstitial atoms, and their clusters) and defect sinks (e.g., dislocation loops, voids, He bubbles).…”
Section: Sluggish Diffusion and Chemically-biased Atomic Transportmentioning
confidence: 99%
“…8,9 The effects of elementally biased defect transport have been revealed by molecular dynamics (MD) simulations showing slow 3D short-range diffusion of small interstitial clusters in NiFe, in contrast to 1D long-range migration in pure Ni and NiCo. 6,[39][40][41] In contrast to a periodic energy landscape in pure metals, the landscape in concentrated alloys is highly distorted by local "traps". 41 Because of atomic-level chemical fluctuations, temporal traps are formed in which defect formation energies are low (i.e., mobile defects spend most of their time in these traps).…”
Section: Sluggish Diffusion and Chemically-biased Atomic Transportmentioning
confidence: 99%
“…Defect configuration and reduction in damage are also reported in similar MD study conducted by Béland et al 55 In addition to the Ni-Fe system, reduction in damage is also found in the NiCo system compared with pure Ni. Béland et al 56 also showed that the difference in the production of large defects between Ni and NiFe is not related to the ballistic of collision cascade. Koch et al 57 studied a chemically more complex SP-CSA, CuNiCoFe.…”
Section: B MD Simulation: Displacement Cascade Evolution and Defect mentioning
confidence: 99%